2022
DOI: 10.3390/foods11162509
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Guava Leaf Polyphenols on Advanced Glycation End Products of Frozen Chicken Meatballs (−18 °C) and Its Mechanism Analysis

Abstract: The inhibitory effect of guava leaf polyphenols (GLP) on advanced glycation end products (AGEs) of frozen chicken meatballs (−18 °C) and its possible inhibitory mechanism was investigated. Compared with control samples after freezing for 6 months, acidic value (AV), lipid peroxides, thiobarbituric acid reactive substance (TBARS), A294, A420, glyoxal (GO), Nε-carboxymethyl-lysine (CML), pentosidine, and fluorescent AGEs of chicken meatballs with GLP decreased by 11.1%, 22.3%, 19.5%, 4.30%, 8.66%, 8.27%, 4.80%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Lipid oxidation was evaluated by measuring the thiobarbituric acid reactive substances (TBARS) referring to [19] with minor alterations. In brief, 2 g of the sample was placed in a stoppered graduated test tube.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Lipid oxidation was evaluated by measuring the thiobarbituric acid reactive substances (TBARS) referring to [19] with minor alterations. In brief, 2 g of the sample was placed in a stoppered graduated test tube.…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…Zhao et al discovered that lipid oxidation generated a substantial number of free radicals, precursors of advanced glycation end products (AGEs) and highly reactive glycation compounds. These substances can react with amino acids or amino groups, thereby enhancing the formation of Maillard reaction products [36]. Francisco et al found that benzaldehyde could be formed through the amino acid degradation pathways initiated by lipid oxidation products [37].…”
Section: Characterization and Analysis Of Oxidized Lipids In Egg Yolk...mentioning
confidence: 99%
“…(2016) found brown seaweed polyphenols can maintain the gel strength of fish mince by retarding lipid and protein oxidation. Additionally, dog rose polyphenols (Utrera et al., 2014) were found to inhibit tryptophan oxidation in beef myofibrillar proteins, while guava leaf polyphenols (Zhao et al., 2022) can delay lipid and protein oxidation and reduce the formation of advanced glycation end products in chicken.…”
Section: Introductionmentioning
confidence: 99%